Evaluation of cyberstalking and its relations with the fear of missing out, the compulsive internet use, and emotional intelligence - Gómez Yepes, Talía (2025)
Cyberstalking is a form of persecution that has spread with the evolution of technology and has gained significant attention in recent years. There are different studies that attempt to investigate variables that could be related to this type of behavior. This research aims to find some validity evidence for the assessment of cyberstalking in the Argentine context. Additionally, it seeks to analyze the relationships between cyberstalking and other emerging digital phenomena, such as Fear of Missing Out (FoMO) and compulsive internet use. The study was conducted with a sample of 1102 participants, with an age range of 18 to 65 years (M = 38.21; SD = 10.45), 53.90 % were identified as female and 46.10 % as male. Regarding the first objective of the study, we observed validity evidence of the cyberstalking scale, confirming its reliability and relevance. Concerning the second objective, the findings provided an analysis between cyberstalking, FoMO, and compulsive internet use. The findings highlight the importance of how compulsive internet use and the fear of missing out are potential factors that favor cyberstalking behaviors. The findings underscore the need for targeted interventions and digital literacy programs aimed at reducing the risk of cyberstalking, especially among vulnerable populations.